Safety of a training program for ultrasound-guided internal jugular vein catheterization in critically ill patients - Dexheimer Neto,Felippe Leopoldo (2011)
OBJECTIVES: Evaluate the safety and effectiveness of a training program for performing ultrasound-guided internal jugular vein cannulation in critically ill patients. METHODS: Cohort prospective study, evaluating adult patients admitted in a teaching intensive care unit (ICU). Catheter placement was performed by an ICU medical resident. The patient's baseline characteristics, vessel's position and operator experience were the evaluated variables. The main outcomes were cannulation success rate and incidence of major complications. RESULTS: A total of 118 consecutive patients were enrolled between May 2008 and November 2009. The success rate of ultrasound guided catheter placement was 90% (106/118), 77% in the first attempt. Major complications occurred in 4% of the cases (n = 5) and were not associated with the analyzed variables. Inability to place the guide wire was the reason for 58% (7/12) of the failures. Operators with more than 15 previous ultrasound guided cannulations had an increased success rate (95% vs. 79%, p = 0.01) and increased failure was related to previous catheterization (26% vs. 7%, p = 0.02). CONCLUSION: Learning ultrasound guidance for IJV vein cannulation was safe and feasible in ICU patients. This process was not associated to complications and better results were achieved across the spectrum of operator experience